Network pharmacology and experimental validation to investigate the mechanism of action of Zhilong Huoxue Tongyu capsule in the prevention and treatment of diabetic cardiomyopathy. - Fang Yang; Gang Luo; Meng-Nan Liu; Ping Liu; Dan Wu; Hao-Ling Chen; Shan Li; Si-Jin Yang; Li Dong (PLoS ONE)
Background Diabetes cardiomyopathy (DCM) is a prevalent complication of diabetes, characterized by a multifaceted pathogenesis. Zhilong Huoxue Tongyu Capsule (ZL), a traditional Chinese medicine, is extensively employed for the treatment of cardiovascular diseases. Thus, this study aimed to comprehensively explore the mechanism of action of ZL on DCM. Method Network pharmacology approaches were applied to predict the potential pathways and targets of ZL on DCM. Then, a DCM model mouse was constructed and divided into a control group, DCM group, DCM + ZL group, SB203580 group, and DCM + R group. The DCM + ZL group was administered 6.24g/kg/d ZL via gavage, the SB203580 group was given 1 mg/kg/d SB203580 (p38MAPK inhibitor) via intraperitoneal injection, the DCM + R group received 4 mg/kg/d rosiglitazone via gavage, and the control group and DCM group were given equal volume of physiological saline by gavage. The intervention period lasted for 6 weeks to verify these key targets. Result Network pharmacology analyses identified 45 active ingredients in ZL linked to 719 potential targets, forming an herbal compound-target network. Screening of databases revealed 1032 DCM-related targets, with MAPK14, TNF, FOS, AKT1, and IL-10 emerging as key hub genes from PPI network analysis. Additionally, enrichment analysis indicated that the candidate targets were enriched in response to the MAPK signaling pathway. Finally, in vivo studies in DCM mice demonstrated that ZL significantly mitigated myocardial fibrosis and down-regulated the expression of p-P38MAPK, TNF-α, α-SMA, and Collagen-I proteins in myocardial tissue. Conclusion Our results collectively indicated that ZL can effectively ameliorate diabetes cardiomyopathy, possibly by modulating the P38MAPK signaling pathway.